2009
DOI: 10.1099/mic.0.028993-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of MexZ and PA5471 in transcriptional regulation of mexXY in Pseudomonas aeruginosa

Abstract: MexXY, a drug efflux pump in Pseudomonas aeruginosa, confers resistance to aminoglycoside antibiotics. We recently reported that MexZ binds to the promoter region of the mexXY operon. Electrophoretic mobility shift assay (EMSA) using recombinant MexZ and oligonucleotide probes prepared from the intergenic region between mexZ and mexX revealed that MexZ binds to a 20 bp palindromic sequence. Culture of P. aeruginosa in the presence of tetracycline induced higher levels of MexX and MexZ, as measured by immunoblo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 39 publications
2
55
0
Order By: Relevance
“…However, chemical agents such as antibiotics, dyes, and ethidium bromide bind to QacR and inactivate the repressor, allowing transcription of the qacA gene to produce the QacA protein (6,17). Similar mechanisms have been proposed for the regulation of the expression of the AcrAB efflux pump of E. coli by the environmental inducer indole and in the aminoglycoside antibiotic-mediated induction of the MexXY efflux pump in Pseudomonas aeruginosa (13,20).…”
Section: Resultsmentioning
confidence: 89%
“…However, chemical agents such as antibiotics, dyes, and ethidium bromide bind to QacR and inactivate the repressor, allowing transcription of the qacA gene to produce the QacA protein (6,17). Similar mechanisms have been proposed for the regulation of the expression of the AcrAB efflux pump of E. coli by the environmental inducer indole and in the aminoglycoside antibiotic-mediated induction of the MexXY efflux pump in Pseudomonas aeruginosa (13,20).…”
Section: Resultsmentioning
confidence: 89%
“…The very low basal expression level of mexXY(oprA) in wild-type bacteria results from the direct binding of the dimerized, strong repressor MexZ to a 20-bp palindromic sequence encompassing the overlapping promoters of mexXY(oprA) and the adjacent, divergently transcribed gene mexZ (458,825,826). Unlike other TetR-type regulators (727), MexZ's DNA binding is not relieved by antibiotics through a direct ligand-regulator interaction but seemingly via indirect protein-protein sequestration, a process relying on the product of the PA5471 gene, named ArmZ, for the antirepressor of mexZ (825)(826)(827). It was demonstrated that the induction of mexXY expression in response to protein synthesis inhibitors is totally dependent upon ArmZ and that the expression of armZ itself is induced by ribosome-targeting agents through a sophisticated mechanism of transcriptional attenuation involving a short 13-amino-acid leader peptide, PA5471.1 (828).…”
Section: P Aeruginosa Efflux Pumpsmentioning
confidence: 99%
“…In spite of these clear disadvantages, nfxB mutants are readily selected following exposure to fluoroquinolones, azithromycin, and even biocides like triclosan both in vitro and during clinical therapy (37,100,168). Another regulator is MexZ, which belongs to the TetR family and normally represses the transcription of the mexXY genes by binding to the mexZmexX intergenic region (157,264). Mutations in MexZ have been found to participate in the acquisition of moderate aminoglycoside resistance in CF isolates of P. aeruginosa (256) and may be a significant cause of impermeability-type aminoglycoside resistance, which occurs in 10% or more of patients treated extensively with aminoglycosides.…”
Section: Mutational Resistance Related To Efflux Pumpsmentioning
confidence: 99%